1983
DOI: 10.1177/002221948301600407
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Nonstrategic Linguistic Coding on Visual Recall of Learning Disabled Readers

Abstract: Three experiments directly investigated Vellutino's (1977) verbal-deficit hypothesis, which suggests reading difficulties of learning disabled children are attributable to deficiencies in linguistic coding. Short-term retention was studied using random shapes to minimize effects of prior verbal learning. Adopting a probe-type serial memory task, normal and LD readers were compared on recall performance after pretraining of named and unnamed stimulus conditions. Recall was markedly better for normal subjects tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In a summary of several of his own studies dealing with verbal and visual coding processes in children with and without reading disabilities, Swanson (1986) concluded that children of average intelligence who have dyslexia fail to use multiple codes in an additive fashion in memory tasks. Swanson's studies showed that label training increases memory for visual forms in skilled readers but seems to reduce recall in children with learning disabilities (Swanson, 1978(Swanson, , 1983(Swanson, , 1984. If children with dyslexia do not derive a memory benefit from using multiple codes, then perhaps the sound-symbol training aspect of phonics instruction only confuses them and interferes with their reading skill development.…”
Section: Deficits In Phonological Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a summary of several of his own studies dealing with verbal and visual coding processes in children with and without reading disabilities, Swanson (1986) concluded that children of average intelligence who have dyslexia fail to use multiple codes in an additive fashion in memory tasks. Swanson's studies showed that label training increases memory for visual forms in skilled readers but seems to reduce recall in children with learning disabilities (Swanson, 1978(Swanson, , 1983(Swanson, , 1984. If children with dyslexia do not derive a memory benefit from using multiple codes, then perhaps the sound-symbol training aspect of phonics instruction only confuses them and interferes with their reading skill development.…”
Section: Deficits In Phonological Perceptionmentioning
confidence: 99%
“…There is some empirical evidence that part of the disability may be in visual perception and memory for the forms of letters or their position in a sequence (Badian, 1998;Cornoldi, Rigoni, Tressoldi, & Vio, 1999;Eden, Stein, Wood, & Wood, 1995;Morrison, Giordani, & Nagy, 1977; Slaghuis, Lovegrove, & Davidson, 1993). Visual limitations associated with dyslexia have also been attributed to perceptual (Badcock & Lovegrove, 1981;DiLollo, Hansen, & McIntyre, 1983;Eden et al, 1995;Enns, Bryson, & Roes, 1995;Gal-aburda & Livingstone, 1993; Slaghuis et al, 1993) and memory processes (Corkin, 1974;Enns et al, 1995;Morrison et al, 1977;Spring & Capps, 1974;Swanson, 1978Swanson, , 1983Swanson, , 1984.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been argued that rehearsal or organization deficits are major problems of students with RD (see Swanson et al, 2004, for literature review), this notion is not held true across all studies. Several earlier studies have reported that differences in STM processes, such as rehearsal or chunking, do not distinguish between students with and without RD (R. L. Cohen, 1981;Swanson, 1983aSwanson, , 1983b. For example, some studies have found significant memory differences between students with and without RD when rehearsal is controlled and stimulus organization is provided (R. L. Cohen, 1981;Swanson, 1983b).…”
mentioning
confidence: 99%